1990
DOI: 10.1111/j.1532-5415.1990.tb01594.x
|View full text |Cite
|
Sign up to set email alerts
|

Informed Consent for Neuroleptics with Elderly Patients in Two Settings

Abstract: This paper presents the results of four studies that evaluated the use of neuroleptics in an aging population both in nursing homes and in a psychiatric teaching hospital. The purpose was to determine the degree to which prescribing practices were in compliance with recent court rulings respecting the right of patients to informed consent to "exceptional" medication. The results indicate that physicians in nursing homes do not inform their patients of the risks of neuroleptics, do not seek consent, and do not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…In evaluating decision making capacity, investigators used as an outcome measure either an assessment of global capacity or a particular capacity criterion. The studies using global measures of capacity 28 , 33 , 37 , 45 , 69 , 77 , demonstrated a range of capacity within the study population, suggesting that certain subsets of the population do need a formal evaluation of decision‐making capacity. The particular criteria evaluated for assessing decision‐making capacity included the rationality of a choice, 31 , 59 , 60 , 79 , 80 patient's appreciation of illness, 31 , 37 , 59 understanding, 23 , 37 , 59 , 97 evidence of a choice, 59 and reasonableness of choice 59 .…”
Section: Resultsmentioning
confidence: 99%
“…In evaluating decision making capacity, investigators used as an outcome measure either an assessment of global capacity or a particular capacity criterion. The studies using global measures of capacity 28 , 33 , 37 , 45 , 69 , 77 , demonstrated a range of capacity within the study population, suggesting that certain subsets of the population do need a formal evaluation of decision‐making capacity. The particular criteria evaluated for assessing decision‐making capacity included the rationality of a choice, 31 , 59 , 60 , 79 , 80 patient's appreciation of illness, 31 , 37 , 59 understanding, 23 , 37 , 59 , 97 evidence of a choice, 59 and reasonableness of choice 59 .…”
Section: Resultsmentioning
confidence: 99%
“…In practice, when adult patients disagree with medical advice, health care providers not infrequently ignore their wishes. Sometimes, health care providers frankly admit that they are ignoring what they regard as an illconsidered decision (Garrison, 2007;Grisso & Appelbaum, 1995;Gurian et al, 1990;Saks & Jeste, 2006;Vars, 2008) and sometimes they are just more willing to challenge a dissenting patient's decision-making capacity (Farnsworth, 1990;Grisso & Appelbaum, 1995).…”
Section: The Rules For Competent Adults and The Preference For Followmentioning
confidence: 99%
“…The identification of 'incapable' patients by clinical staff is not optimal and even when staff recognised patients' incapacity to give informed consent, proper legal procedures for appointing surrogate decision makers are not generally followed (Barton et al, 1996). In fact, the usual practice, as reported from a survey of Massachusetts nursing homes, is the presumption of capacity until a patient fails to acquiesce to treatment and only at that point is the issue of capacity fully addressed (Gurian et al, 1990). Gurian et al (1990) concluded that informed consent for neuroleptics was not considered an issue and that decision making capacity was not being tested.…”
Section: Introductionmentioning
confidence: 97%
“…In fact, the usual practice, as reported from a survey of Massachusetts nursing homes, is the presumption of capacity until a patient fails to acquiesce to treatment and only at that point is the issue of capacity fully addressed (Gurian et al, 1990). Gurian et al (1990) concluded that informed consent for neuroleptics was not considered an issue and that decision making capacity was not being tested.…”
Section: Introductionmentioning
confidence: 97%